2021
DOI: 10.1016/j.bbr.2021.113189
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically stable neurotensin analogs exert potent and long-acting analgesia without hypothermia

Abstract: Highlights § Incorporation of reduced amide bond, silaproline and TMSAla in NT(8-13) resulted in JMV5296, a 25-fold NTS2-selective analog. § Combination of these three chemical modifications increased resistance toward proteases having a plasma stability over 20 hours. § Intrathecal injection of JMV5296 induced potent antinociception in acute, tonic and chronic inflammatory pain models. § Central delivery of JMV5296 had no impact on body temperature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…98 The NTSR1 agonist PD149163 and the NTSR1 PAM PP-001 (structures not disclosed), both produced analgesia in acute and chronic pain models in rats. 99,100 As mentioned previously, both NTSR1 and NTSR2 agonists produce analgesia, however, the adverse effects of neurotensin such as hypothermia and hypotension are mediated via NTSR1 activation. 100 It was recently reported that the selective NTSR2 agonists JMV431 (63) produced antinociception in the tail-flick, formalin, and CFA tests in rats without inducing hypothermia.…”
Section: Nonsteroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 89%
See 2 more Smart Citations
“…98 The NTSR1 agonist PD149163 and the NTSR1 PAM PP-001 (structures not disclosed), both produced analgesia in acute and chronic pain models in rats. 99,100 As mentioned previously, both NTSR1 and NTSR2 agonists produce analgesia, however, the adverse effects of neurotensin such as hypothermia and hypotension are mediated via NTSR1 activation. 100 It was recently reported that the selective NTSR2 agonists JMV431 (63) produced antinociception in the tail-flick, formalin, and CFA tests in rats without inducing hypothermia.…”
Section: Nonsteroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 89%
“…The NTSR1 agonist PD149163 and the NTSR1 PAM PP-001 (structures not disclosed), both produced analgesia in acute and chronic pain models in rats. , As mentioned previously, both NTSR1 and NTSR2 agonists produce analgesia, however, the adverse effects of neurotensin such as hypothermia and hypotension are mediated via NTSR1 activation . It was recently reported that the selective NTSR2 agonists JMV431 ( 63 ) produced antinociception in the tail-flick, formalin, and CFA tests in rats without inducing hypothermia . CGX-1160 (structure not disclosed), a neurotensin A analogue, produced antinociception in a phase Ia clinical trial in patients with central neuropathic pain following spinal cord injury .…”
Section: Approaches To Develop Safer Ligands For New Pain Targetsmentioning
confidence: 90%
See 1 more Smart Citation
“…Numerous NTS 1 targeting ligands carrying the pharmacophore NT­(8-13) hexapeptide sequence (H-Arg-Arg-Pro-Tyr-Ile-Leu-OH) , have been developed and studied in different types of peripheral tumors, such as colorectal cancer, prostate adenocarcinoma, breast cancer, or pancreatic cancer. Contrarily, NTS 2 targeting peptides have been studied for their central opioid-independent analgesic potency. Whereas very few analogues have been developed for imaging of peripheral tumors, NTS 2 ’s role in tumor development remains unclear and requires more investigations. Indeed, in prostate cancer, NTS 2 mRNA expression was found only in malignant well-differentiated (androgen receptors +) cell-lines .…”
Section: Introductionmentioning
confidence: 99%
“…8 − 12 Contrarily, NTS 2 targeting peptides have been studied for their central opioid-independent analgesic potency. 13 17 Whereas very few analogues have been developed for imaging of peripheral tumors, 18 NTS 2 ’s role in tumor development remains unclear and requires more investigations. Indeed, in prostate cancer, NTS 2 mRNA expression was found only in malignant well-differentiated (androgen receptors +) cell-lines.…”
Section: Introductionmentioning
confidence: 99%